2010
DOI: 10.1007/s12192-010-0189-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs associated with hyperthermia-induced cellular stress response

Abstract: MicroRNAs (miRNAs) are a class of small RNAs that play a critical role in the coordination of fundamental cellular processes. Recent studies suggest that miRNAs participate in the cellular stress response (CSR), but their specific involvement remains unclear. In this study, we identify a group of thermally regulated miRNAs (TRMs) that are associated with the CSR. Using miRNA microarrays, we show that dermal fibroblasts differentially express 123 miRNAs when exposed to hyperthermia. Interestingly, only 27 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 61 publications
(86 reference statements)
3
65
0
Order By: Relevance
“…As hyperthermia and oxidative stresses are the two major mechanisms for the varicocele-related spermatogenesis damage, we first selected five miRNAs (namely miR-15a, miR-16, miR-18a, miR-192, and miR-320) which were reported to be implicated in hyperthermia or oxidative cellular stresses , Ren et al 2009, Wilmink et al 2010. The expressions of these miRNAs in the ejaculated spermatozoa of ten pairs of patients with varicocele and the healthy donors were investigated by qRT-PCR.…”
Section: Expressions Of Stress-related Mirnas In the Ejaculated Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…As hyperthermia and oxidative stresses are the two major mechanisms for the varicocele-related spermatogenesis damage, we first selected five miRNAs (namely miR-15a, miR-16, miR-18a, miR-192, and miR-320) which were reported to be implicated in hyperthermia or oxidative cellular stresses , Ren et al 2009, Wilmink et al 2010. The expressions of these miRNAs in the ejaculated spermatozoa of ten pairs of patients with varicocele and the healthy donors were investigated by qRT-PCR.…”
Section: Expressions Of Stress-related Mirnas In the Ejaculated Spermmentioning
confidence: 99%
“…The miRNAs-mediated stress responses play important roles in plenty of human diseases, such as infection, cardiovascular disease, and cancer (Leung & Sharp 2010, Mendell & Olson 2012. Previous studies have shown that miR-15a, miR-16, miR-18, miR-192, and miR-320 are involved in hyperthermia or oxidative cellular stresses , Ren et al 2009, Wilmink et al 2010. However, the roles of miRNAs on varicocele-related stress environment remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…hsa-miR-34a, hsa-miR-125b, hsa-miR-128, hsa-miR-146a, hsa-miR-205, hsa-miR-221 and hsa-miR-432 were thermally upregulated whereas one miRNA (hsa-miR-154) was thermally downregulated [15] . Interestingly, hsa-miR-34a and hsa-miR-125b were earlier reported to be induced by heat shock in human dermal fibroblast [8] . The same study also reported heat shock-driven decreased hsa-miR-154 expression [8] , as also observed by us.…”
Section: Research Highlightmentioning
confidence: 98%
“…[6,7] . Over the years, active involvement of miRNAs in response to different stress stimuli including hyperthermia [8] , hypoxia [9] , ER stress [10] etc. has been reported.…”
mentioning
confidence: 99%
“…[14][15][16] In comparison to scalpel incisions, those made by lasers in surgery generally have the disadvantage of causing a delay in wound healing due to collateral thermal damage to surrounding tissues. This was demonstrated in a study where differences in gene expression between free electron laser (FEL) and scalpel incisions in mouse skin were analyzed.…”
Section: Introductionmentioning
confidence: 99%